(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This work presents a technique for design optimization of a gas turbine tubular combustor. This technique is based on the use of computational fluid dynamics (CFD) with CFX solver to reduce emission gases by using multi-line of fuel injection in secondary zone. This research relates the mass fraction of the multi-line of fuel injection as well as the equivalence ratio of the tubular combustion chamber designed for methane fuel. By using k-ε as turbulent model and Probability Density Function (PDF) Flamelet as combustion model. The operating casing data of micro size gas turbine are used, the validation of fuel flow mixing and combustion analyses were carried out with a focus on species concentration in the combustor outlet section. With variant fuel mass flow rate fraction in fuel lines (F2/F1), It was found that, with the new design NO reduced about 56% for the mass fraction 3 in high equivalence ratio and about 30%for the mass fraction 1 for a low equivalence ratio, while reduction in outlet temperature profile (pattern factor) is about 45% → 35%.